2009
DOI: 10.1016/j.mvr.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity causes cerebral vessel remodeling and increases the damage caused by ischemic stroke

Abstract: Hypertension, elevated fasting blood glucose and plasma insulin develop in rats fed a high fat (HF) diet. Our goal was to assess the effects of obesity, beginning in childhood, on the adult cardiovascular system. We hypothesized that rats fed a HF diet would have larger ischemic cerebral infarcts and middle cerebral artery (MCA) remodeling. Three-week-old male Sprague Dawley rats were fed a HF (Obese) or control diet for 10 weeks. Cerebral ischemia was induced by MCA occlusion (MCAO). MCA structure was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 39 publications
(47 reference statements)
5
63
2
Order By: Relevance
“…Experimental studies have shown that either HFD or genetically induced obesity was accompanied by increased cerebrovascular remodeling, promoted hypertension, and increased infarct size in either transient or permanent focal ischemia models (7,32). HFD-fed apoEϪ/Ϫ mice with hyperlipidemia also had increased infarct volume (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental studies have shown that either HFD or genetically induced obesity was accompanied by increased cerebrovascular remodeling, promoted hypertension, and increased infarct size in either transient or permanent focal ischemia models (7,32). HFD-fed apoEϪ/Ϫ mice with hyperlipidemia also had increased infarct volume (23).…”
Section: Discussionmentioning
confidence: 99%
“…Given that stroke is the leading cause of disability and that the obesity epidemic is on the rise these clinical and social problems are expected to get worse, and therefore early interventions are necessary. While experimental studies in genetic or diet-induced obesity models have shown increased cerebral infarct size and poor outcomes of stroke (7,25,32,33,41), the early impact of a high-fat diet (HFD) before the development of obesity on AIS injury and functional outcomes is not known.It is known that the brain relies heavily on constant blood flow for proper function. Two important mechanisms that contribute to the regulation of cerebral blood perfusion are autoregulatory behavior of cerebral vessels and functional hyperemia upon increased neuronal activity (11,16,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, other studies have also reported that adult offspring of HFD-fed dams can have normal glucose tolerance and body composition (Miotto et al 2013, Platt et al 2014. More specifically, although numerous studies have indicated the cerebrovascular hazards of an increased intake of dietary fat in adults (Langdon et al 2011) or beginning in childhood (Deutsch et al 2009), it remains to be established whether HFD consumption during pregnancy and the suckling period can influence the cerebrovascular health of adult offspring.…”
Section: Introductionmentioning
confidence: 99%